Implementation and Challenges of Jail Services in District Jails in Western Visayas, Philippines - Ermee Joy F. Painaga; Jasmin L. Parreño (Philippine Social Science Journal, 2025)
Utilizing a quantitative descriptive-comparative design with 153 Persons Deprived of Liberty (PDLs) in Antique, Philippines, this study assessed the implementation of essential jail services during the 2023–2024 fiscal year. The findings revealed a "very great extent" of overall implementation, validating Scheirer’s (1987) Program and Implementation Theory, as service levels varied significantly based on situational factors such as population, budget, location, and personnel. While voting assistance was rated highest, insufficient ventilation remained the primary challenge, highlighting disparities that specifically disadvantage smaller jails. Consequently, the study urges the Bureau of Jail Management and Penology to pursue strategic NGO partnerships and targeted resource allocation to ensure consistent service delivery, while suggesting that future research employ qualitative methods to investigate the underlying causes of implementation gaps and their long-term impact on rehabilitation.